Efeito da ingestão aguda de taurina sobre o desempenho físico e metabolismo lipídico de nadadores de elite de Ribeirão Preto - Dato, Carla Cristina [UNESP] (2014)
Taurine is an amino acid found in various tissues is derived from the metabolism of methionine and cysteine. This amino acid has different beneficial functions, including osmoregulation, modulation of ionic calcium, stabilizing the plasma membrane, nervous system development, immunomodulation and antioxidant activity. Furthermore, studies have shown an association between taurine improves physical performance and increased levels of lipolysis, indicating an improvement in metabolic efficiency. The peak maximum stay concentration of taurine in the circulation is 120 minutes. Thus, the aim of this study was to determine whether supplementation with taurine acutely 120 minutes before exercise improves physical performance and causes an increase in the release of lipids in swimmers. To investigate this proposal a double-blind study was conducted with the participation of 10 elite swimmers male aged 21 years 17e, which were submitted to two analyzes of maximum performance in the 400m semi-Olympic pool. For performance evaluation we analyzed the lactate peak, for the levels of lipolysis was measured in serum glycerol, and the adequacy of nutrition food records were applied. A significant 24% increase in plasma level of lipolysis in swimmers supplemented with taurine, however no significant increase in physical performance of athletes or changes in lactate. It is concluded that acute taurine supplementation 120 minutes before a maximal exercise test carries an improvement in metabolic efficiency of lipids when combined with exercise, but chronic studies are needed to verify the role of this action on the physical performance of the athlete.